1996
DOI: 10.1002/(sici)1096-9063(199601)46:1<49::aid-ps340>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Sterols that modify moulting in insects

Abstract: Abstract:The development of insects is under the control of a steroid hormone, ecdysone. This paper reviews suicide substrate type inactivators designed to inhibit the biosynthesis of ecdysone. Several series of acetylenic derivatives of cholesterol were synthesized and their biological effects on the prothoracic glands of the locust were investigated in oitro, enabling structure-activity relationships to be studied.Information on the ability of brassinosteroids, a series of plant growth regulators, to inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…However, it is interesting to note that in the BR-deficient cpd mutant, the expression of pathogenesis related genes is greatly reduced (107). Little further work has been done on the effects of BRs as herbicide safeners (49,112,113), but interest in the interactions of BRs with insects (16,83) continues, with the object of using BR-analogues as antiecdysones (65).…”
Section: Modulation Of Stress Responsesmentioning
confidence: 99%
“…However, it is interesting to note that in the BR-deficient cpd mutant, the expression of pathogenesis related genes is greatly reduced (107). Little further work has been done on the effects of BRs as herbicide safeners (49,112,113), but interest in the interactions of BRs with insects (16,83) continues, with the object of using BR-analogues as antiecdysones (65).…”
Section: Modulation Of Stress Responsesmentioning
confidence: 99%
“…Scheme 14 Modifications to the steroid side-chain in fungi, plants and insects (numbers refer to characteristic side-chains of certain sterols -nucleus not specified). i, si-face methylation by SMT; ii, re-face hydride migration by SMT; iii, SMT; iv, 24 -reductase inhibition 1282 and P-450 monooxygenases involved in biosynthesis have been reviewed. 1283 The dietary or endogenous origin of ecdysteroids in gastropods remains an open question.…”
Section: Biosynthesis Of Steroids In Insectsmentioning
confidence: 99%
“…8 By comparing molecular models of 1 and 2 it was found that the 3b-hydroxyl group of 1 and the 3a-hydroxyl group of 2 occupied the same space ( Fig. 1) and this might lead to effective competition in binding the ecdysteroid receptor of 2.…”
Section: Introductionmentioning
confidence: 98%